The short-term effects of antenna insulation thickness on path losses in wireless telemetry implants at microwave frequencies - Lukas Kneisz; Michael Schermann; Ewald Unger; Michael Haller; Matthias Krenn; Winfried Mayr (PAGEPress Publications, 2013)
Various physiological parameters can be monitored non-invasively using wireless biotelemetry links. The development of sophisticated ultra low power consuming transceivers allows the transmission of large amounts of data from the inside of the body to an external receiver in real time at microwave frequencies.Antenna impedance matching is crucial for obtaining an acceptable propagation link budget in a wireless telemetry link. The dielectric properties of biological tissue induce detuning to transceiver antennas when implanted into the body. To counteract detuning problems, implant antennas are coated with biocompatible insulating material. The study investigates the propagation losses of a wireless communication link at different insulation thicknesses of medical grade silicone in the Industrial-Scientific-Medical (ISM) radio band at 2.45 GHz. The wireless link consisted of an implantable unit which was placed between two pads of tissue substitute material and an external receiver which was connected to a laptop. Predefined data packets were transmitted from the implant, the received packets were analyzed, packet errors and packet losses were logged and the received signal strength indicator values (RSSI) were recorded. Our results showed that the mean RSSI values of insulated transmitter antennas - embedded in tissue equivalent material - provide more safety distance to critical receiver sensitivity level than uncoated antennas.The conducted measurements let us conclude that with increasing thickness of the insulation layer, the antenna becomes less sensitive to detuning by adjacent tissue substitute material. Therefore tuned antennas are less influenced by the surrounding tissue after implantation.